ABOUT THE FORMATION OF THE DEVELOPMENT COSTS OF THE AIRCRAFT - I. V. Artemenko; V. S. Oleshko; V. M. Samoylenko (Научный вестник МГТУ ГА)
The article discusses approaches to the formation of the limit prices of aircraft with using of elements of economic-mathematical modeling. Theoretical and practical aspects of development of methods of solving economic problems in the implementation of the mechanism of formation of effective innovation-stimulating prices in the drafting and design of aircraft.